2017
DOI: 10.1007/s10143-017-0908-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliable diagnosis of IDH-mutant glioblastoma by 2-hydroxyglutarate detection: a study by 3-T magnetic resonance spectroscopy

Abstract: We have previously reported that reliable detection of 2-hydroxyglutarate (2HG) in isocitrate dehydrogenase (IDH)-mutant WHO grade 2 and 3 gliomas is possible utilizing 3.0-T single-voxel magnetic resonance spectroscopy (SVMRS). We set out to determine whether the same method could be applied to detect 2HG in IDH-mutant glioblastoma. Forty-four patients harboring glioblastoma underwent pre-operative MRS evaluation to detect 2HG and other metabolites. Presence of IDH-mutations was determined by IDH1 R132H immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
4
24
0
2
Order By: Relevance
“…Among the in vivo techniques, 1 H MRS appears to be the most promising tool for the identification of IDH1 mutant gliomas by highlighting higher levels of 2-HG in these tumors. [12][13][14] However, this method has demonstrated a relatively high incidence of false positive results, ranging from 18.5% to 26%. 15 Nowadays, a number of structural and functional parameters, such as vascular density, vessel size index (VSI), cerebral blood flow (CBF), blood volume fraction (BVf), tumor oxygenation (tissue oxygen saturation (StO 2 )), and cerebral metabolic rate of oxygen (CMRO 2 ), as well as blood-brain barrier integrity (using a dynamic contrast enhanced (DCE) approach with time to peak (TTP) and signal contrast enhancement), are accessible by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Among the in vivo techniques, 1 H MRS appears to be the most promising tool for the identification of IDH1 mutant gliomas by highlighting higher levels of 2-HG in these tumors. [12][13][14] However, this method has demonstrated a relatively high incidence of false positive results, ranging from 18.5% to 26%. 15 Nowadays, a number of structural and functional parameters, such as vascular density, vessel size index (VSI), cerebral blood flow (CBF), blood volume fraction (BVf), tumor oxygenation (tissue oxygen saturation (StO 2 )), and cerebral metabolic rate of oxygen (CMRO 2 ), as well as blood-brain barrier integrity (using a dynamic contrast enhanced (DCE) approach with time to peak (TTP) and signal contrast enhancement), are accessible by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) may have such a role as an important noninvasive tool for prediction of IDH mutant glioma; however, no MRI techniques have shown impressive results for predicting IDH mutant glioma except for 2-hydroxyglutarate (2HG) MR spectroscopy (MRS). 2HG MRS was introduced to detect the oncometabolite 2HG, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] which occurs as a direct consequence of an IDH mutation. In previous studies, 2HG MRS demonstrated higher diagnostic performance (high sensitivities of 89-100% and high specificities of 81-88%) 10,18 than conventional MRI (sensitivities of 71-100% and specificities of 51-100%) [20][21][22] and diffusionweighted imaging and perfusion-weighted imaging (sensitivities of 56-100% and specificities of 63-100%).…”
mentioning
confidence: 99%
“…This was the first report to describe the relationship between false-positive 2HG measurement and high lactate concentration (7). It is well-known that such high lactate concentrations are associated with necrosis (6,24); therefore, the interpretation of 2HG concentration in patients with .01 3.9 (1.6, 9.4) ,.01 ADC (3 10 23 mm 2 /sec) 0.2 (0.0, 1.4) .10 0.1 (0.0, 0.7)…”
Section: Association Between 2hg Concentration and Lactate Concentrationmentioning
confidence: 89%